FINANCIAL LITERACY, RETURN EXPECTATIONS, Z-GENERATION STOCK INVESTMENT DECISIONS WITH HERDING MODERATION (JABE (Journal of Applied Business and Economic), 2024)
Investing has become a popular method for saving, especially for long-term goals, due to the potential for greater returns over time. Indonesian people are increasingly aware of passive income, especially after the Covid-19 pandemic. Financial technology and online platforms allow more people to manage their investment portfolios. This paper examines the influence of financial literacy. It returns expectations on Z-Generation stock investment decisions and the influence of moderation of herding behavior on financial literacy and returns expectations influencing Z-Generation stock investment decisions. The type of research applied in this research is a quantitative approach. The population in this study is Z-Generation, who registered with the Investkuy stock investment education community on January 12, 2024, with a population of 339 people. The research results show that financial literacy positively affects Z-Generation's stock investment decisions, while return expectations also have a positive effect. However, herding behavior weakens the influence of financial literacy on these decisions while strengthening the influence of expected returns